Towards an efficient system for hyperthermia treatment of breast tumors. (January 2022) - Nizam-Uddin, N.; Abdulkawi, Wazie M.; Elshafiey, Ibrahim; Sheta, Abdel-Fattah A.
Abstract: This study is directed toward the establishment of a simplified experimental setup to investigate the rise in temperature in a microwave hyperthermia treatment system. The setup is established in a closed room to maintain isolation and shielding of the operating system to ensure safety of the operator and to proscribe radiation interference. The proposed system is illustrated by numerical simulations of breast phantom to investigate energy propagation in tissue layers at various excitation frequencies. A novel, water propellant, flexible, foam-based applicator element is designed and fabricated to radiate efficiently in the medium under test. The radiating capabilities of the fabricated element are investigated for various medium properties. A phased array optimization tool is proposed to maximize the deposition of specific absorption rate ( SAR ) distribution at multi-lesions simultaneously. Signal generation, processing and control is performed by configuring software defined radio units under LabView environment. Power amplifier modules are maintained to operate in the linear mode to avoid distortion towards SAR distribution. Temperature rise in the medium under test is quantified experimentally, confirming the feasibility of adopted testbed for hyperthermia applications. The obtained results suggest the efficacy of this system in hyperthermia treatment of breast tumors.